2006
DOI: 10.3164/jcbn.38.107
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of Amino Acids, Oxidized by Reactive Oxygen Species and an Antibody against N-Formylkynurenine

Abstract: Summary Amino acid oxidation, resulting from oxidative stress, is related to certain diseases and aging. To correlate reactive oxygen species with oxidized products of individual amino acids, we oxidized Met, Trp, His, and Tyr by treatment with singlet oxygen, superoxide, or hydroxyl radicals. The structures of oxidized amino acids were determined by nuclear magnetic resonance spectroscopy, infra-red spectroscopy, and fast atom bombardment-mass spectrometry. Among the compounds identified, N-formylkynurenine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
0
8
0
2
Order By: Relevance
“…GDS 2000 ® is likely to negatively affect fingerprint material due to its strong alkaline properties, while BDS 2000 ® , bleach, and SDF ® are able to oxidize components from both the eccrine and sebaceous secretions. A number of publications report the oxidation of the structural group and various side chains of amino acids . Unsaturated fatty acids are also susceptible toward oxidation .…”
Section: Discussionmentioning
confidence: 99%
“…GDS 2000 ® is likely to negatively affect fingerprint material due to its strong alkaline properties, while BDS 2000 ® , bleach, and SDF ® are able to oxidize components from both the eccrine and sebaceous secretions. A number of publications report the oxidation of the structural group and various side chains of amino acids . Unsaturated fatty acids are also susceptible toward oxidation .…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, neither could detect NFK in photooxidized myoglobin (data not shown). A recent paper [28] describes an antibody produced by blocking the α-amine group of tryptophan, oxidizing it with 1 O 2 and then conjugating the resulting product to a carrier protein. This antiserum recognized photooxidized protein, but was used at a dilution of 1:50, a concentration likely to prohibit its wide-spread application due to non-specific binding in complex protein mixtures.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] Visible light interaction with photosensitizers primarily produces singlet oxygen. [4][5][6][7][8] One study on the sensitizer-mediated photooxidation of free His suggested that multiple degradants of His form in the presence of singlet oxygen including oxygenated and crosslinked His arising from unstable His peroxide intermediates. 8 The authors identified the major free His photodegradant using nuclear magnetic resonance and electron paramagnetic resonance spectroscopy as a cyclized two-ring structure, 6a-hydroxy-2-oxooctahydro-pyrollo [2,3-d]imidazole-5-carboxylic acid, with mass (M + 1) of 188 Da.…”
Section: Introductionmentioning
confidence: 99%